ANALISIS FINANSIAL USAHA PENGOLAHAN MANISAN RUMPUT LAUT DI KELURAHAN BONTANG KUALA KECAMATAN BONTANG UTARA KOTA BONTANG - Nur Isnaniah Justika; Bambang Indratno Gunawan; Muhammad Syafril (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
The purpose of the study was to determine the financial feasibility of the candied seaweed processing business based on the components of the investment criteria and to determine the sensitivity level of the candied seaweed processing business to changes in financial aspects. This research was carried out in Bontang Kuala Village, North Bontang District, Bontang City. The samples used were candied seaweed processors totaling 10 people. The sampling method used is purposive sampling. The data analysis method used is financial analysis and sensitivity analysis. The results showed that the candied seaweed processing business in Bontang Kuala Village is financially feasible and prospective to continue to run based on the results of financial analysis, the NPV (Net Present Value) of Rp. 38,557,209, IRR (Internal Rate of Return) of 18%, Net Benefit Cost Ratio of 1.3 times and Payback Period of 5.96 years (71.463 months). and the results of sensitivity analysis (sensitivity analysis), showed that the business of processing candied seaweed in Bontang Kuala Village, was sensitive to changes in economic conditions at OM Costs Up 20%, Production Down 15%, OM Costs Up 10%, Prices Down, Prices Down Rp. 8,500 and OM Costs Up 5% Production Down 5%. Keywords: Candied Seaweed, Financial Analysis, Sensitivity Analysis (Sensitivity Analysis)